The lived experience of Iranian adults from coronavirus disease 2019 (COVID-19)—A qualitative study - Pourmoradian, Samira; Haghighian-Roudsari, Arezoo; Khoubbin Khoshnazar, Tahereh Alsadat; Milani-Bonab, Ali (Frontiers in Public Health, 2025)
IntroductionThe widespread impact of the coronavirus disease 2019 (COVID-19) epidemic on human health causes sudden lifestyle changes, through social distancing and isolation at home, with social and economic consequences. This qualitative study aimed to identify the lived experiences of recovered adult patients from COVID-19 in Iran.MethodsThis qualitative research was conducted using a national phenomenological approach. The participants were patients who recovered from COVID-19 through their treatment period in the hospital or at home. Semi-structured in-depth interviews were applied for 45 participants who were invited using purposeful sampling and continued to achieve data saturation. The five-stage inductive process to analyze the structure of lived experience (IPSE) approach was used to analyze the data using MAXQDA 2020 software.ResultsAccording to the statements of the participants in the study, five types of experiences extracted during the period of suffering from the disease: nutritional problems, physical problems, the psychological burden caused by the disease, the supporting role of others in the disease tolerance, and the unpleasant and better experiences of the disease.DiscussionPatients with COVID-19 disease experience many physical and psychosocial consequences which affect their quality of life. Therefore, sociopsychological support provided by psychologists and family members can have ameliorating effects in reducing disease consequences. Further interventional studies were needed to capture these aspects of diseases.